Treatment of stage I–III periodontitis—The EFP S3 level clinical practice guideline. (27th July 2020) - Sanz, Mariano; Herrera, David; Kebschull, Moritz; Chapple, Iain; Jepsen, Søren; Beglundh, Tord; Sculean, Anton; Tonetti, Maurizio S.; ,
Abstract: Background: The recently introduced 2017 World Workshop on the classification of periodontitis, incorporating stages and grades of disease, aims to link disease classification with approaches to prevention and treatment, as it describes not only disease severity and extent but also the degree of complexity and an individual's risk. There is, therefore, a need for evidence‐based clinical guidelines providing recommendations to treat periodontitis. Aim: The objective of the current project was to develop a S3 Level Clinical Practice Guideline (CPG) for the treatment of Stage I–III periodontitis. Material and Methods: This S3 CPG was developed under the auspices of the European Federation of Periodontology (EFP), following the methodological guidance of the Association of Scientific Medical Societies in Germany and the Grading of Recommendations Assessment, Development and Evaluation (GRADE). The rigorous and transparent process included synthesis of relevant research in 15 specifically commissioned systematic reviews, evaluation of the quality and strength of evidence, the formulation of specific recommendations and consensus, on those recommendations, by leading experts and a broad base of stakeholders. Results: The S3 CPG approaches the treatment of periodontitis (stages I, II and III) using a pre‐established stepwise approach to therapy that, depending on the disease stage, should be incremental, each including different interventions. Consensus was achieved on recommendations covering different interventions, aimed at (a) behavioural changes, supragingival biofilm, gingival inflammation and risk factor control; (b) supra‐ and sub‐gingival instrumentation, with and without adjunctive therapies; (c) different types of periodontal surgical interventions; and (d) the necessary supportive periodontal care to extend benefits over time. Conclusion: This S3 guideline informs clinical practice, health systems, policymakers and, indirectly, the public on the available and most effective modalities to treat periodontitis and to maintain a healthy dentition for a lifetime, according to the available evidence at the time of publication.